Expiratory pattern and laryngeal responses to single-breath expiratory resistance loads - Daubenspeck, J.Andrew; Bartlett, Donald (Respiration physiology, 1983)
Responses of expiratory duration (T E) and laryngeal aperture to small flow resistance loads (2 and 5 cm H 2O/LPS) applied to single expirations were measured using repeated applications in four subjects during quiet breathing. All subjects significantly prolonged T E in response to the higher load and 3 of the 4 showed that same response to the lower load, which was not perceived by these subjects. These same 3 subjects showed a narrowed laryngeal aperture in response to loading such that their expiratory impedance must have been greater than the increase provided by the load alone. The effect of such a loading response was to slow the expiratory volume decay so that a small but significantly increase in the halftime for volume decay was observed. The prolongation of T E seen with loading could be due to the alteration of volume-related feedback consequent to the increased expiratory impedance. This may serve a role in regulation of expiratory muscle function.